Hubungan Self Efficacy Dengan Quarter Life Crisis Dalam Pembelajaran Pada Mahasiswa Keperawatan Di Universitas Murni - Siburian, Sry Gunawan; Simatupang, Lenny Lusia (Universitas Murni Teguh, 2025)
Quarter life crisis is a psychological condition where there is an emotional crisis inindividuals in early adulthood. Students are one of the individuals who are in early adulthoodand are affected by quarter life crisis. At this time, students face challenges in learning. Self-efficacy can give someone confidence in facing life and motivate themselves to be able toface challenges. The purpose of this study was to determine the relationship between self-efficacy and quarter life crisis in learning in nursing students at Murni Teguh University. Thistype of research is quantitative with a correlational approach. Sampling using stratifiedrandom sampling of 71 respondents. Data analysis using Spearman's rho correlation test.The results of this study indicate that there is a significant relationship between self-efficacyand quarter life crisis in learning with a p-value = 0.003 (p <0.05) and a correlation coefficient= -0.342. There is a significant relationship between self-efficacy and quarter life crisis inlearning and both have a negative relationship where if self-efficacy is high then the quarterlife crisis in learning will be low or vice versa. It is recommended for further researchers toadd research variables such as self-esteem and self-confidence with a larger number ofsamples.